Algebra and trigonometry - Abramson, Jay (Livonia , Michigan : XanEdu, 2017)
Welcome to Algebra and Trigonometry, an OpenStax College resource. This textbook has been created with several goals in mind: accessibility, customization, and student engagement - all while encouraging toward high levels of academic scholarship.
1. Prerequisites -- 2. Equations and Inequalities -- 3. Functions -- 4. Linear Functions -- 5. Polynomial and rational functions -- 6. Exponential and Logarithmic -- 7. The Unit Circle: Sine and Cosine Functions -- 8. Periodic Functions -- 9. Trigonometric Identities and equations -- 10. Further Applications of trigonometry -- 11. Systems and equations and Inequalities -- 12. Analytics -- 13. Sequences, Probability and counting theory.
Includes index.
Keywords: ALGEBRA